2003
DOI: 10.1108/09555340310493036
|View full text |Cite
|
Sign up to set email alerts
|

When cultures collide: the challenge of global integration

Abstract: Chrysler are but a few examples. In the sixyear period from 1992 to 1998, the volume of merger deals increased from a modest $58 billion a year to $2.7 trillion worldwide (Rattner, 1999, p. A22). Many, if not most, of these mergers were motivated, at least in part, by the threats and opportunities of globalization. France's Alcatel recently acquired Texas-based DSC Communications and California-based Access Technologies. Sweden's Pharmacia merged with the Upjohn Company of Michigan, and Barnsandnoble.com is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…The Daimler-Chrysler merger is a well-known example of how synergies were used to justify the merger, but where such synergies have been difficult to find (Shelton et al 2004). It is interesting to note that while this article was being written, DaimlerChrysler was also facing a breakup, and the discussion around this case is very similar to that of BMPF.…”
Section: Dynamicsmentioning
confidence: 92%
“…The Daimler-Chrysler merger is a well-known example of how synergies were used to justify the merger, but where such synergies have been difficult to find (Shelton et al 2004). It is interesting to note that while this article was being written, DaimlerChrysler was also facing a breakup, and the discussion around this case is very similar to that of BMPF.…”
Section: Dynamicsmentioning
confidence: 92%
“…A more recent global survey by KPMG (Colin & Spitzer, 2001) reported that 70 percent of the combinations studied failed to add value. Shelton, Hall and Darling (2003) noted that two-thirds of the M&A transactions they considered destroyed shareholder value, primarily because of intended synergies not being realised. Other studies held a similar view that, while the target shareholders generally fare well, most acquisitions fail to create value for acquirers (Carr et al 2005;Hazelkorn, Zenner & Shivdasani 2004;Mamdani & Noah 2004;Vester 2002;).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a worldwide survey in 1998/99 by Watson Wyatt, retention of talent, communication and integration of cultures were rated as the three most critical activities in the integration plan (Devine 2002). Poor cultural fit or lack of cultural compatibility have become much-cited reasons for M&A failure (Beard & Zuniga 2006;Bijlsma-Frankema 2001;Cartwright & Schoenberg 2006;Huang & Kleiner 2004;Lynch & Lind 2002;Shelton et al 2003;Teerikangas & Very 2006). Furthermore a by-product of many, if not most M&As, is that, target firm executives experience considerable stress causing an average of almost 70 percent to depart in the five years following completion (Schraeder & Self 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, these cultural differences in many ways were the foundation for the mutual attraction between the two companies. The Germans admired the entrepreneurial spirit and innovative thinking of the Chrysler team, while Chrysler folks respected the methodological engineering savvy of the Germans (Shelton, Hall, and Darling, 2003). Based on the above observations, it is clear that they didn't just make cars differently; they lived in different worlds (Badrtalei -Bates, 2007).…”
Section: An Important Success Factor: the Speed Of Integration (Soi)mentioning
confidence: 99%
“…Without such a value base, it was impossible to identify a core purpose and create a win-win vision for cultural integration. (Shelton -Hall -Darling, 2003).…”
Section: An Important Success Factor: the Speed Of Integration (Soi)mentioning
confidence: 99%